EFFECT OF CREDIT RISK ON PROFITABILITY OF PUNJAB NATIONAL BANK - Kapoor, Bhisham; Kapoor, Bhisham; Sanyam, (International Journal of Psychosocial Rehabilitation, 2020)
Punjab National Bank is one of the top leading public sector banks in India. Credit risk is one of the oldest and greatest risks of a bank. These days Punjab National Bank is facing a big problem of credit risk. The NPAs of Punjab National Bank is increasing year on year due to which it had to suffer loss during previous few years. The study attempts to identify and implementation of credit risk management and also to analyze the effect of credit risk on profitability of Punjab national bank. With the help of secondary data collected from the Punjab National Bank’s annual report for last two years the effect of NPAs on profitability was analyzed. Correlation coefficient was used to analyze the effect of credit risk on the profitability of PNB. The study has an immense use to meet consumer needs and to face competition with other banks. The major reason of increased NPAs is the focus of bank on quantitative aspect of target attainment and less attention is being paid to the qualitative aspect of loan disbursement and mismanagement of funds. The synonym is also coming in that bank is no longer able to recover their NPAs because of which it has to face loss instead of profits. Now is the time when bank needs to focus more on its NPAs management.